The Effect Of Giving Rewards On Mathematics Learning Outcomes Of Class V Primary School Students - Darinda Sofia Tanjung; Juli Ana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to determine the effect of giving rewards on the mathematics learning outcomes of fifth grade elementary school students at 097388 village Partuhan, Simalungun Regency, in the 2021/2022 academic year. The population of this study were all students in grades 5a and 5b of SD Negeri 097388 in the village of Partuhan, totaling 62 students. The research method used in this research is an experimental method with a quantitative research type. The instrument used to collect data is in the form of multiple choice questions and questionnaires. The results of this study indicate that student learning outcomes using the reward method are in the very good category with an average of 83.2. This researcher used the normality test with the results of 0.200 > 0.05 or L count > L table. Based on these calculations, it can be seen that the significant value is normally distributed. In the correlation test, the coefficient value of 0.710 means that r count > r table 0.250. So there is a strong influence between the method of giving rewards to the mathematics learning outcomes of 5th grade elementary school students at 097388 village partuhan. The results of the t-test are 7.803 > 1.679 so it is accepted. this shows that there is a significant positive effect of the effect of giving rewards on the mathematics learning outcomes of 5th graders at SD Negeri 097388 Partuhan Village in the 2021/2022 academic year. Keywords:Giving rewards, mathematics, learning outcomesThis study aims to determine the effect of giving rewards on the mathematics learning outcomes of fifth grade elementary school students at 097388 village Partuhan, Simalungun Regency, in the 2021/2022 academic year. The population of this study were all students in grades 5a and 5b of SD Negeri 097388 in the village of Partuhan, totaling 62 students. The research method used in this research is an experimental method with a quantitative research type. The instrument used to collect data is in the form of multiple choice questions and questionnaires. The results of this study indicate that student learning outcomes using the reward method are in the very good category with an average of 83.2. This researcher used the normality test with the results of 0.200 > 0.05 or L count > L table. Based on these calculations, it can be seen that the significant value is normally distributed. In the correlation test, the coefficient value of 0.710 means that r count > r table 0.250. So there is a strong influence between the method of giving rewards to the mathematics learning outcomes of 5th grade elementary school students at 097388 village partuhan. The results of the t-test are 7.803 > 1.679 so it is accepted. this shows that there is a significant positive effect of the effect of giving rewards on the mathematics learning outcomes of 5th graders at SD Negeri 097388 Partuhan Village in the 2021/2022 academic year.